Implementasi Program Selasa Bagarakan Terhadap Psikomotorik Dan Kreativitas Siswa di Sekolah Dasar - Ridhatul Jannah; Ahmad Suriansyah; Arta Mulya Budi Harsono (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Psychomotor development plays a crucial role in children's growth, providing positive influences that encompass various aspects of life. Freedom for students to hone their skills based on their interests and talents can foster creativity, which is a key factor in helping students think creatively and develop creative skills. This study aims to explore the phenomenon in depth in a limited context regarding the implementation of the Bagarakan Tuesday program on students' psychomotor skills and creativity at UPTD SDN 2 Kait-kait without treatment intervention. This study uses a qualitative approach with a case study design. The researcher uses semistructured interviews, non-participatory observation, and document study as data sources. The research sample consists of 1 program coordinator. The results of data analysis show that psychomotor and creativity development have a positive influence on students at UPTD SDN 2 Kait-kait.